ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMAKAIAN JASA ASURANSI JIWA PADA AJB BUMIPUTERA 1912 KANTOR CABANG BATURAJA - Hema Malini; Safaruddin; Devi Novia Utami Putri (Jurnal Humaniora & Sosial Sains, 2024)
In developing and increasing sales of life insurance business, it is important to know the factors that influence the decision to use life insurance. The research method used is quantitative descriptive. The results of multiple linear regression indicate a positive relationship between income, age, continuity funds with the decision to use life insurance services at AJB Bumiputera 1912 Baturaja Branch Office. The correlation coefficient obtained a value of r = 0.476 that the relationship between income, age and continuity funds on the decision to use life insurance services is positive and stated to be very strong. The determination coefficient with a value of 0.227 indicates that the decision to use life insurance services is influenced by income, age and continuity funds by 22.7% while the remaining 77.3% is influenced by other factors not examined in this study. The results of the income hypothesis test obtained a t-count value of -0.163, so there is no significant influence of income on the decision to use life insurance services, while on the continuity fund the t-count value is 2.892, so there is a significant influence of continuity funds on the decision to use life insurance services and simultaneously there is a significant influence between income, age and continuity funds together on the variable decision to use services.